Community Analysis of a Crisis Response Network. (June 2021) - Kim, Yushim; Kim, Jihong; Oh, Seong Soo; Kim, Sang-Wook; Ku, Minyoung; Cha, Jaehyuk
This article distinguishes between clique family subgroups and communities in a crisis response network. Then, we examine the way organizations interacted to achieve a common goal by employing community analysis of an epidemic response network in Korea in 2015. The results indicate that the network split into two groups: core response communities in one group and supportive functional communities in the other. The core response communities include organizations across government jurisdictions, sectors, and geographic locations. Other communities are confined geographically, homogenous functionally, or both. We also find that whenever intergovernmental relations were present in communities, the member connectivity was low, even if intersectoral relations appeared together within them.